2012
DOI: 10.4103/0970-9290.107380
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some salivary characteristics between children with and without early childhood caries

Abstract: The higher mean resting salivary pH and better buffering capacity found in children without ECC are probably the contributing factors that protect against caries development; but further studies are needed to understand the effects of saliva and its characteristics and components on ECC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 1 publication
3
40
0
9
Order By: Relevance
“…20 Furthermore, various studies have shown that altered salivary pH, BC and ALP levels are associated with the formation or development of dental caries, gingivitis, periodontitis, human immunodeficiency virus (HIV) infection, diabetes, orthodontic tooth movements, cancer, abdominal inflammatory diseases and the early onset of menopause. 3,4,12,13,[21][22][23][24][25][26][27][28][29] In the current study, salivary pH was lower among smokers in comparison to non-smokers; although the mean values found seem to reflect a minimal difference between the two groups (7.42 versus 7.52, respectively), even very small alterations in pH can influence salivary enzyme activity. 6 Additionally, BC was significant lower among smokers in the current study.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…20 Furthermore, various studies have shown that altered salivary pH, BC and ALP levels are associated with the formation or development of dental caries, gingivitis, periodontitis, human immunodeficiency virus (HIV) infection, diabetes, orthodontic tooth movements, cancer, abdominal inflammatory diseases and the early onset of menopause. 3,4,12,13,[21][22][23][24][25][26][27][28][29] In the current study, salivary pH was lower among smokers in comparison to non-smokers; although the mean values found seem to reflect a minimal difference between the two groups (7.42 versus 7.52, respectively), even very small alterations in pH can influence salivary enzyme activity. 6 Additionally, BC was significant lower among smokers in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…12 Bagherian et al reported lower pH and BC values among children without caries. 13 In contrast, another study indicated lower resting salivary pH values among individuals with dental caries.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Different results reported that there was no difference in total sIgA concentrations in caries-free children with children having caries experience≥ 5 [27]. Bagherian & Asadikaram [34] reported the opposite results that the highest total sIgA concentration was owned by ECC children (196.14 ± 100.07 mg/dl) than in caries-free children (148.45 ± 81.26 mg/dl; p=0.015).…”
Section: Literature Review a Secretory Immunoglobulin A And The mentioning
confidence: 95%
“…From several studies, it can be concluded that there was a relationship between sIgA concentration and caries incidence [21,33,34], therefore sIgA concentrations could be developed as an ECC risk assessment biomarker.…”
Section: Literature Review a Secretory Immunoglobulin A And The mentioning
confidence: 99%